P492 Predicting chlamydia reinfection in african american women using immunogenetic determinants in a Bayesian model. (14th July 2019) - Olson, Kristin; Geisler, William; Tiwari, Hemant
Abstract : Background: African Americans have the highest rates of Chlamydia trachomatis (CT) infection in the U.S., nearly six-fold higher than Caucasians. Even after controlling for sociodemographic factors, African American women have higher CT infection rates, suggesting immunogenetic factors could influence infection risk. The primary objective of this study is to develop a Bayesian model to predict CT reinfection in African American women. Methods: We are using data from a study cohort of CT-infected women who were enrolled when they returned to a STD clinic in Birmingham, AL, USA, for treatment of a positive screening urogenital CT nucleic acid amplification test. They had repeat urogenital CT NAAT performed at enrollment and 3- and 6-month follow-up visits. We modeled the probability of CT reinfection within 6 months after treatment using conditional logistic regression in a Bayesian framework and weakly informative priors. Primary predictors of interest were immunogenetic risk factors specified by the presence of at least one HLA-DQB1*06 allele and absence of a CT-specific CD4 + IFN-γ response. Additional predictors evaluated include the modifying effects of unprotected sex and concomitant bacterial vaginosis (BV). Results: To date, we have evaluated 75 participants for whom complete data were available. Modeling both HLA-DQB1*06 and a CT-specific CD4 + IFN-γ response performed best for expected predictive accuracy of CT reinfection within 6 months after treatment. Under this model, the probability of reinfection for those with a CT-specific CD4 + IFN-γ response and no HLA-DQB1*06 alleles was 23.1% (95% CI: 7.6%–47.5%), whereas probability of reinfection for those without a CT-specific CD4 + IFN-γ response and at least one HLA-DQB1*06 allele was 75.0% (95% CI: 52.5%–89.1%). Conclusion: Our model evaluating immunogenetic factors predicting CT reinfection demonstrated that presence of an HLA-DQB1*06 allele and absence of a CT-specific CD4 + IFN-γ response may be a significant predictor in African American women. Disclosure: No significant relationships.